Penerapan Media Video dengan Model E-Learning (Daring) dalam Upaya Meningkatkan Hasil Belajar IPS Materi Globalisasi dan Nasionalisme pada Siswa Kelas IX MTs Negeri 9 Aceh Timur Tahun Pelajaran 2020/2021 - Khairul Amri (Departement of Mathematics Education, 2021)
This research is an effort to Improve Social Studies Learning Outcomes through the E-Learning Model with Video Media for Class IX Students at MTs Negeri 9 Aceh Timur. Giving assignments without any learning materials delivered by the teacher causes social studies learning outcomes to be relatively low or still below the KBM, which is 75. This study uses Classroom Action Research (CAR) in the form of implementing an e-learning model with video media with the aim of improving student learning outcomes for Class IX MTs Negeri 9 Aceh Timur which consists of two cycles and each cycle consists of planning, implementing, observing, and reflecting. The research subjects were students of Class IX of MTs Negeri 9 Aceh Timur. The number of students was 29 students, consisting of 10 male students and 19 female students. The results showed that the application of the e-learning model with video media could improve social studies learning outcomes for Class IX students of MTs Negeri 9 Aceh Timur. Judging from the results of the pre-cycle students who completed KBM only 14 students (48.3%) and 15 students (51 ,7%) which has not been completed. In the first cycle there are 24 students (82.8%) who have completed and 5 students (17.2%) have not completed, and in the second cycle there are 26 students (89.7%) who have completed and there are 3 students (10.3 %) unfinished. From the increase in learning outcomes, this classroom action research was stopped in cycle II because it had achieved the classical completeness criteria, namely 85% of the total number of students who had completed learning and were declared successful in improving social studies learning outcomes for Class IX students of MTs Negeri 9 Aceh Timur in the 2020/2021 academic year. .